ANALISIS KEPUASAN KERJA KARYAWAN: PENGARUH LINGKUNGAN KERJA DAN BEBAN KERJA (STUDI PADA NAILOGY BALI) - Ni Luh Putu Yuli Ayu Warsiki; Anak Agung Ngurah Gede Sadiartha; I Gede Aryana Mahayasa (Warmadewa Management and Business Journal (WMBJ), 2025)
Job satisfaction greatly affects employee work results so that it is maximum, so it is important to maintain it, factors that have an influence on employee job satisfaction, namely the work environment and employee workload. This study serves to determine the partial and simultaneous influence of the work environment and employee workload on employee job satisfaction in Nailogy Bali Ubung and Canggu. The number of samples in this study is all Nailogy Bali Ubung and Canggu employees totaling 34 respondents. The method of determining the sample with a saturated sample is that the entire population is used as a sample. This study uses a quantitative approach, namely by distributing questionnaires to respondents. The data analysis technique uses multiple linear regression analysis. The results of this study were obtained that 1) The work environment has a positive and significant effect on the job satisfaction of Nailogy Bali Ubung and Canggu employees. 2) Workload has a negative and significant effect on the job satisfaction of Nailogy Bali Ubung and Canggu employees and 3) The work environment and workload simultaneously affect the job satisfaction of Nailogy Bali Ubung and Canggu employees. The advice in this study to maintain employee job satisfaction is to provide a comfortable work environment and supervise employees so that they do not feel a high workload during work.